المرأة في فكر مالك بن نبي - شيخة مبروك, نور الهدى; بن غريبي, رقية (University of eloued جامعة الوادي, 2021)
"تهدف الدراسة الموسومة ""المرأة في فكر مالك بن نبي"" إلى إبراز مكانة المرأة عند هذا المفكر، وبالأخص تحديد وجهة نطره التي عمل على الدفاع عنها، وارتباطها واسهامها في توطين السلوك الحضاري والصورة المثالية لنشرها لدعوتها في ظل ماشهده العالم من تطورات وانعكاسها على المجتمع، اضافة لاعتبار المرأة القاطرة الأساسية لنهوض أي أمة. فمع هذا فإن الموضوع يهدف للتعرف على شخصية ""مالك بن نبي"" واكتشاف أفكاره نحو قضايا المرأة وتوسيع للاستفادة من حركتها الحضارية. وبعد اطلاعنا على هذا البحث توصلنا إلى أهم نتيجة، وهي تحديد معالم رؤية مالك بن نبي للمرأة وموقع مشكلتها ضمن الحضارة، ومدى تأثير دعوته. كما نوصى ونقترح في نهاية البحث بدخول المرأة في مجال العمل ولكن في مجالات خاصة ومعينة كالتعليم وغيرها. ""The study titled ""The Woman in the Thought of Malik Bin Nabi"" aims to highlight the position of women in this thinker, and in particular to determine the direction of his adversity, which he worked to defend, and its connection and contribution to the localization of civilized behavior and the ideal image for spreading her call in light of the developments witnessed by the world and its reflection on society, as well as Considering women the basic locomotive for the advancement of any nation. Nevertheless, the topic aims to get to know the personality of ""Malik"" and discover his ideas about women's issues and expand the benefits of her civilization movement. After examining this research, we reached the most important result, which is to define the parameters of Malik bin Nabi's vision for women, the location of her problem within the problems of civilization, and the extent of the impact of his call. We also recommend and suggest, at the end of the research, that women enter the field of work, but in special and specific fields such as education and others. "
دعوة
Keywords: مالك بن نبي؛ المرأة، الفكر.; Malik Bennabi; Woman, thought.